Willingness of tobacco retailers in Oyo State to participate in tobacco control programmes (2018)
INTRODUCTION Tobacco control strategies have not incorporated retailers, despite being the focus by the tobacco industry to promote its products. Few studies exist on their possible roles in tobacco control. This study, therefore, assessed retailer awareness of tobacco control laws and willingness to be involved in control activities. METHODS A cross sectional study was carried out on all 218 tobacco retailers in Ibarapa Central and Ibarapa East Local Government Areas of Oyo State. The willingness of tobacco retailers to participate in tobacco-use control was evaluated using a questionnaire. RESULTS The majority of the respondents were females (95%), and 30-39 years old with respect to age. Almost two-thirds (65%) of the respondents reported the sale of tobacco as a profitable business, and a third reported that their income would decrease if they stopped tobacco sales. Up to 35% of retailers were aware of laws restricting smoking in public places and 45% aware of a ban on the sale of tobacco products to minors. Retailers were willing to: support anti-tobacco legislations (84%), counsel smokers to quit smoking (84%), and display anti-tobacco messages in their shops (77%). CONCLUSIONS The sale of tobacco products is a profitable venture for retailers. Willingness to participate in tobacco control was high among the retailers. There is a need to raise awareness and co-opt tobacco retailers as change agents in tobacco control efforts.